Development of Accuracy Shooting Training Tools in Futsal Games - Teddy Rudy Harto Sianturi; Budi Valianto; Nurhayati Simatupang (UNIB Press, 2022)
The purpose of this study was to develop accuracy shooting training tools in futsal games for extracurricular players in (SMP) Subdistrict, Medan Labuhan. In this study using the R&D Model according to Borg and Gall. The aids have been assembled then validated by 2 experts. Material experts, and trainer experts. The initial trial of the field is 8 players, the main field trial is 30 players. The form of tools that have been created is validated in advance by 1 material expert, 1 expert coach has a background in sports education. So, based on the validation results by experts, it can be concluded that the accuracy shooting training tool in the futsal game is valid and can be used for training in the futsal game.